2023
DOI: 10.3390/v15081662
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of SARS-CoV-2 Antibody Titer Multiplied by Binding Avidity of Receptor-Binding Domain (RBD) in Monitoring Protective Immunity and Clinical Severity

Abstract: Conventional serum antibody titer, which expresses antibody level, does not provide antigen binding avidity of the variable region of the antibody, which is essential for the defense response to infection. Here, we quantified anti-SARS-CoV-2 antibody binding avidity to the receptor-binding domain (RBD) by competitive binding-inhibition activity (IC50) between SARS-CoV-2 S1 antigen immobilized on the DCP microarray and various RBD doses added to serum and expressed as 1/IC50 nM. The binding avidity analyzed und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Staerke et al showed that this was true for the Delta variant of SARS-CoV-2, but the risk of breakthrough infection with Omicron was not related to anti-S IgG concentrations [49]. Although some efforts have been put towards establishing an antibody protective titer [51,[54][55][56], neither a universal cut-off for protection nor a definition of a "high" antibody concentration have been proposed yet. Dimeglio et al reported that anti-S-RBD antibody concentrations of 1700 BAU/mL and above provided full protection in subjects followed-up for a median of 275 days (ca.…”
Section: Discussionmentioning
confidence: 99%
“…Staerke et al showed that this was true for the Delta variant of SARS-CoV-2, but the risk of breakthrough infection with Omicron was not related to anti-S IgG concentrations [49]. Although some efforts have been put towards establishing an antibody protective titer [51,[54][55][56], neither a universal cut-off for protection nor a definition of a "high" antibody concentration have been proposed yet. Dimeglio et al reported that anti-S-RBD antibody concentrations of 1700 BAU/mL and above provided full protection in subjects followed-up for a median of 275 days (ca.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these samples showed a statistically higher mean S-based avidity of 126.4% and lower NCP-based avidity of 11.0% compared to samples from April 2020 onward (S t-test=2.4, p=0.01; NCP t-test=-2.9, p=0.007; Figure 1E and 1F). High avidity to the S protein is reached 1-2 months after SARS-CoV-2 infection and is maintained for approximately 6-8 months (8,9). High S-based avidity would thus suggest very early SARS-CoV-2 infection in patients sampled during January 2020, contrasting with calculated SARS-CoV-2 phylogenetic introduction estimates and the first SARS-CoV-2 molecular detections in Latin America dating from February 2020 onwards (10).…”
Section: Importancementioning
confidence: 92%